Tree Detection for Urban Environment Using Watershed Segmentation (International Journal of Engineering and Computer Science, 2014)
Devastation of trees at urban level is expanding quickly which is prompting incredible natural anxiety. This needs to be controlled to save and keep up the environmental offset of earth. Exact urban vegetation information is obliged to oversee green assets so regions can keep the track of the venture done in urban ranger service exercises. The study exhibits a methodology to gauge the tree populace by dividing the VHR information with the assistance of marker controlled watershed algorithm. It sections all the trees and different objects uniquely. Implementation on the basis of texture algorithm, color based algorithm, mean shift algorithm and threshold can also be performed.